2021
DOI: 10.1177/23259671211031240
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Responsiveness of the Anterior Cruciate Ligament Return to Sport After Injury (ACL-RSI) Scale

Abstract: Background: The Anterior Cruciate Ligament Return to Sport After Injury (ACL-RSI) scale is a reliable and valid tool for evaluation of psychological readiness to return to sport after ACL injury, but its responsiveness to change has not been extensively evaluated. Purpose: To determine the responsiveness of the ACL-RSI scale. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: The ACL-RSI scale and the knee confidence question from the Knee injury and Osteoarthritis Outcome Score–Quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…For that reason, in addition to the traditional knee outcome scores, several studies created new scores or modifications of preexisting scores to assess the psychological aspects after injury and reconstruction such as the Tampa Scale for Kinesophobia, Emotional Responses of Athletes to Injury Questionnaire, Profile of Mood States, and ACL-Return to Sport Injury Scale. 26,30 Patient-reported psychological readiness, subjective feeling of knee stability, and pain-free return to sporting movements were considered by some participants as some of the most important RTS criteria. The current study revealed that even when the participants considered that these subjective factors play an essential role, most of them did not use PROMs or a specific score to assess psychological factors in the RTS decision e6 making.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For that reason, in addition to the traditional knee outcome scores, several studies created new scores or modifications of preexisting scores to assess the psychological aspects after injury and reconstruction such as the Tampa Scale for Kinesophobia, Emotional Responses of Athletes to Injury Questionnaire, Profile of Mood States, and ACL-Return to Sport Injury Scale. 26,30 Patient-reported psychological readiness, subjective feeling of knee stability, and pain-free return to sporting movements were considered by some participants as some of the most important RTS criteria. The current study revealed that even when the participants considered that these subjective factors play an essential role, most of them did not use PROMs or a specific score to assess psychological factors in the RTS decision e6 making.…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, in addition to the traditional knee outcome scores, several studies created new scores or modifications of preexisting scores to assess the psychological aspects after injury and reconstruction such as the Tampa Scale for Kinesophobia, Emotional Responses of Athletes to Injury Questionnaire, Profile of Mood States, and ACL-Return to Sport Injury Scale. 26 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis was performed using the IBM SPSS Statistics for Windows, version 25, 2017 (IBM Corp., Armonk, N.Y., USA). The sample-size calculation was made for the main outcome (ACL-RSI at the 18-month follow-up), where the estimated mean was based on data in a previous study [ 35 ]. A sample-size calculation showed that a total sample size of 72 patients were required to be able to identify a 13.4-point difference, corresponding to the minimal detectable change (MDC) [ 35 ] between groups with 80% power at an alpha level of 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…The ACL–Return to Sport after Injury scale (ACL-RSI) is considered a reliable tool to assess psychological readiness to return to sport after ACL surgery [ 17 , 18 ]. It has been demonstrated that patients with lower ACL-RSI scores are at higher risk for ACL re-rupture [ 19 ], and recently much emphasis is given to the recovery of psychological responses as a criterion used to clear athletes to return to sport following ACL reconstruction.…”
Section: Introductionmentioning
confidence: 99%